Coping with uncertainty in the assessment of atmospheric pollution with lichen transplants. Issue 3 (3rd July 2019) - Loppi, Stefano; Ravera, Sonia; Paoli, Luca
Abstract: In the assessment of atmospheric deposition using lichen transplants, coping with uncertainty is mandatory in cases of environmental forensics, when understanding whether an area is polluted or not, or tracing a given pollution source is of paramount importance. In this article, we have suggested a method based on the calculation of exposed-to-control ratios of element concentrations and on the quantification of the overall uncertainty associated with such calculation, which proved to be very robust and can be applied in most cases using a minimum of three replicates. The method allowed the selection of significantly accumulated elements i.e. those polluting the site under study, as well as the evaluation of whether a site is significantly polluted or not. We recommend the use of this evaluation method in biomonitoring studies based on transplanted samples.